DETERMINATION OF WATER QUALITY STATUS BASED ON HEAVY METAL CONTENTS IN THE RAINY AND DRY SEASON USING THE STORET INDEX IN PASURUAN SEA WATERS, EAST JAVA - Endang Yuli Herawati; Diana Arfiati; Pratama Diffi Samuel; Karina Farkha Dina; Putri Anugerah; Rahmi Valina (JFMR (Journal of Fisheries and Marine Research), 2021)
Waters that are presumably contaminated with heavy metals need to be observed to ensure the level of pollution to perform water restoration. This study was aimed to determine the status of water quality based on heavy metal contents. The survey method was employed in this study, and it was conducted in Pasuruan sea waters in different seasons; September 2019 represented the dry season, and April 2020 represented the rainy season. The water sampling stations were chosen by using purposive sampling in three sampling locations: the sea waters of Kraton, Lekok, and Nguling districts. The heavy metals and water quality parameters were analyzed by using Storet Index. The results indicated that the highest level of heavy metals was found in Lekok waters in September, consisting of Hg (1.22 mg/l), Cd (1.20 mg/l), and Pb (0.55 mg / l). The seawater of Nguling district had the lowest content in April, while Kraton's seawater was moderate. The water quality status based on the Storet Index suggested that the sea waters of Kraton, Lekok, and Nguling districts were classified as moderately polluted with a score of -16 to -24. The highest score was in September in the rainy season with a score of -24 and the score in April in the dry season was -16. It means that the score is increasing but still in the moderately polluted category. The measurement results of temperature, pH, dissolved oxygen, salinity, and current velocity were in optimum results for aquatic organisms in the dry season or the rainy season. Regarding the water quality status in Pasuruan sea waters, it can be concluded that the heavy metal contents exceeded the quality standard set by the government. Therefore, improved management is required to prevent the deterioration of the pollution status in Pasuruan sea waters